2021
DOI: 10.1101/2021.02.27.21252572
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Burden of Post-COVID-19 Syndrome and Implications for Healthcare Service Planning: A Population-based Cohort Study

Abstract: ObjectiveTo assess the prevalence of impaired health status and physical and mental health symptoms among individuals at least six months after SARS-CoV-2 infection, and to characterise their healthcare utilisation.DesignPopulation-based prospective cohort study.SettingZurich SARS-CoV-2 Cohort, Zurich, Switzerland.Participants431 adults from the general population with PCR-confirmed SARS-CoV-2 infection reported to health authorities between 27 February 2020 and 05 August 2020.Main outcome measuresWe assessed … Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
86
1
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 83 publications
(96 citation statements)
references
References 31 publications
8
86
1
1
Order By: Relevance
“…In our study 23% of COVID-positive required at least one additional medical visit for COVID-19-related symptoms, which is close to the proportion of 36% found in another study (16).…”
Section: Discussionsupporting
confidence: 88%
See 3 more Smart Citations
“…In our study 23% of COVID-positive required at least one additional medical visit for COVID-19-related symptoms, which is close to the proportion of 36% found in another study (16).…”
Section: Discussionsupporting
confidence: 88%
“…In a systematic review and meta-analysis of studies evaluating the prevalence of persisting symptoms up to 110 days after COVID-19 of various severities, the five more common symptoms were fatigue (58%), headache (44%), attention disorder (27%), hair loss (25%) and dyspnea (24%), while agueusia, anosmia and memory loss were reported by 23%, 21% and 16% of the studies populations (24). Two studies evaluating hundreds of laboratory-confirmed COVID-19 outpatients have reported the prevalence of symptoms lasting more than 6 months after diagnosis: 33-39% participants with at least one symptom, 14-55% with fatigue, 22% with dyspnea, and 14% with loss of sense of smell or taste (15,16).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…190 Understanding the needs of these patients will allow for the development of healthcare, rehabilitation, and other resources needed to support their recovery. 191,192 However, identifying patient needs is contingent on developing a research infrastructure that accurately assesses the natural history of this illness.…”
Section: Importance Of Defining Long Covidmentioning
confidence: 99%